Review of Nonstationary and Nonlinear Heating of a Spherical Body Rotating in a Viscous Fluid with a Constant Angular Velocity - Ebtekar, Sayed Sarwar (Journal of Natural Sciences – Kabul University, 2024)
This study investigates the steady rotation of a sphere in a viscous fluid with constant angular velocity, a phenomenon crucial for understanding thermal instability in rotating systems affected by viscosity. Theoretical analysis reveals that temperature increase at the sphere's surface, at the fluid-solid interface, is unstable and leads to spontaneous temperature escalation. We demonstrate that this temperature increase is a nonlinear process. Furthermore, we establish that the sphere's surface temperature should rise due to frictional effects as it moves through the dense medium. Employing the Navier-Stokes equations and the unsteady heat equation, we elucidate the significantly nonlinear nature of the unsteady heat process. Finally, we derive a general formula for fluid flows and present the results graphically.